THE IMPACT OF STEP AEROBICS EXERCISES ON THE PHYSICAL CONDITION OF HIGHER EDUCATION STUDENTS - Shkolа Olena; Volkova , Elizaveta (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article addresses the issue of improving the physical fitness level of higher education students in conditions of reduced physical activity. The results of a pedagogical experiment aimed at assessing the effectiveness of step aerobics exercises in the physical education system are presented. The purpose of the study was to determine the impact of systematic step aerobics training on key indicators of students’ physical condition. The study involved higher education students aged 18–22 who participated in an eight-week training program using a step platform. Physical condition was assessed based on indicators of aerobic endurance, muscular strength, flexibility, coordination abilities, and fatigue levels. The findings revealed statistically significant improvements in all measured parameters in the experimental group compared to the control group. The results confirm the feasibility of implementing step aerobics as an effective and accessible means of optimizing physical education in higher education institutions.